Pengaruh Return On Assets (ROA) dan Return On Equity (ROE) Terhadap Pertumbuhan Laba pada PT. Kalbe Farma Tbk Periode Tahun 2009-2019 - Andrian Anhar (Publikasi Indonesia, 2023)
This study aims to determine whether return on aseets and return on equity have an influence on profit growth in kalbe farma tbk companies in 2009 – 2019. The research design used was associative causality with samples obtained using purposive sampling, with a total sample of 44 samples